Rock Manning goes for broke - Anders, Charlie (Burton, MI : Subterranean Press, 2018)
When their films become the escapist fun that society needs in a world of violence and destruction, Rock Manning and Sally Hamster are approached by a fascist militia known as the Red Bandanas, to star in their propaganda films promoting their movement.
Keywords: Comedians -- United States -- Fiction; Comedians -- United States -- Fiction; Politics -- Fiction; United States -- Politics and government -- Fiction; United States -- Social conditions -- Fiction; United States -- Politics and government -- Fiction; United States -- Social conditions -- Fiction; Fantasy fiction; Political fiction; Fantasy fiction